2007
DOI: 10.1074/jbc.m703066200
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Cancer Cell Migration

Abstract: In contrast, SP600125, a JNK MAPK inhibitor, had no effect on migration. Knockdown of p38 MAPK using short interfering RNA blocked IGFBP-6-induced migration of RD cells. These results indicate that p38 MAPK is involved in IGFBP-6-induced IGF-independent RD cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Transcriptome analysis between NAC1-expressing SKOV3 human ovarian cancer cells and NAC1-siRNA silenced SKOV3 cells demonstrated that several genes differentially expressed by NAC1 were involved in cell migration [34]. These include forkhead box Q1 ( FOXQ1 ) [34], insulin-like growth factor-binding protein-6 ( IGFBP6 ) [35], chemokine (C-X-C motif) ligand 1 (CXCL1, also known as GROα) [36], drebrin-like protein ( DBNL , also known as mammalian actin-binding protein-1) [37], and Rho-associated, coiled-coil-containing protein kinase 2 (ROCK2) [38]. Further work will be required to define the precise nature of the signaling cascades linking NAC1 to these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis between NAC1-expressing SKOV3 human ovarian cancer cells and NAC1-siRNA silenced SKOV3 cells demonstrated that several genes differentially expressed by NAC1 were involved in cell migration [34]. These include forkhead box Q1 ( FOXQ1 ) [34], insulin-like growth factor-binding protein-6 ( IGFBP6 ) [35], chemokine (C-X-C motif) ligand 1 (CXCL1, also known as GROα) [36], drebrin-like protein ( DBNL , also known as mammalian actin-binding protein-1) [37], and Rho-associated, coiled-coil-containing protein kinase 2 (ROCK2) [38]. Further work will be required to define the precise nature of the signaling cascades linking NAC1 to these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the principal function of circulating IGFBP-3, in addition to the transport of IGFs, is the protection of the IGFs from rapid clearance and/or degradation [4]. At the cellular level, it has become clear that IGFBPs 1–6 have intrinsic biological activity (i.e., IGF/IGF-1R-independent actions) in addition to binding of IGFs, sequestering active hormones, and limiting IGF biological activity [5], [6]. These intrinsic cellular actions include proliferation, differentiation, migration, angiogenesis, and apoptosis in an IGF/IGF-1 receptor (IGF-1R)-independent manner [1], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor binding protein 6 (IGFBP6) and glioblastoma amplified sequence (GBAS) are over-expressed in PAP-RCC. IGF binding proteins are biomarkers for several types of cancer [15]. GBAS is a likely target for tyrosine kinases that is co-amplified in some cancers with epidermal growth factor receptor (EGFR) [16].…”
Section: Section III Results and Discussionmentioning
confidence: 99%